1990
DOI: 10.1007/bf01728790
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis in young people: Evaluation of 57 cases diagnosed before the age of 40

Abstract: Over the past 13 years 57 cases of primary thrombocytosis in young people have been studied. Only patients with a platelet count over 500 x 10(9)/liter and a follow-up longer than 2 years were considered. Thrombocytosis in young people represents approximately 25% of total cases referred to our department during this period. The most common causes are essential thrombocythemia (20 cases) and secondary thrombocytosis (22 cases). The highest platelet counts are found in essential thrombocythemia patients. Most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…The frequency of complications increased with older age. But serious complications and ET-related deaths were also observed in young patients of our study and of other reports (Millard et al, 1990;Mitus et al, 1990;Randi et al, 1990). This may be relevant for therapeutic decisions, despite the good overall prognosis.…”
Section: Discussionsupporting
confidence: 79%
“…The frequency of complications increased with older age. But serious complications and ET-related deaths were also observed in young patients of our study and of other reports (Millard et al, 1990;Mitus et al, 1990;Randi et al, 1990). This may be relevant for therapeutic decisions, despite the good overall prognosis.…”
Section: Discussionsupporting
confidence: 79%
“…With the advent of automated platelet counting, PT is diagnosed with increasing fre- [25,31,40,43,48]. While it was initially suggested that PT might have a more benign course in younger patients [25], several studies since then [31,40,43,48] have demonstrated that PT in young patients may result in serious and life-threatening hemostatic complications. In general, the major causes of mortality and morbidity in PT are attributed to thrombohemorrhagic sequelae [6,13,14,16,21,24,27,47,49,59].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…PT has usually been considered a disease of the middle aged, with its onset in the fifth to sixth decades of life and a slight female preponderance (Table 2) [6,13,14,16,21,24,27,[47][48][49]59]. With the advent of automated platelet counting, PT is diagnosed with increasing fre- [25,31,40,43,48].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Some authors 8,9 define thrombocythemia as a longlasting and very pronounced thrombocytosis (more than 1000 X 10 9 /L), others use the term "thrombocythemia"corresponding to the term leukemia-when thrombocytosis is caused by an autonomous defect of stem cells, for example in myeloproliferative disorders. 10,11 More practical is the classification of thrombocytoses according to their origin into primary and secondary forms. An increase in platelet count generally has one of three causes: (1) A primary disorder, such as a myeloproliferative or myelodysplastic syndrome, which is classified as primary thrombocytosis; (2) an increased production due to stimuli (a prolonged survival time of platelets as cause for thrombocytosis has not yet been described); or (3) a shift of platelets from the splenic pool into the peripheral circulation.…”
Section: Terminology and Classificationmentioning
confidence: 99%